2023
DOI: 10.1088/2053-1591/acd227
|View full text |Cite
|
Sign up to set email alerts
|

Study of a novel cross linked graft copolymer starch in water-based drilling fluid

Abstract: In the drilling industry, the demand for environmentally friendly additives with high thermal stability is increasing due to the dual factors of increasing environmental pressure and high-temperature oil layers. However, commonly used non-toxic and biodegradable additives, such as etherified modified starch, cannot withstand temperatures higher than 150 °C. Additionally, natural polymers with better thermal stability obtained through graft modification with sulfonated monomers face challenges in meeting the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The remarkable advantages of starch nanosphere, such as insignificant influence on rheology, outstanding filtration control at elevated temperatures and high biocompatibility, make it a promising filtrate reducer in high-performance water-based drilling fluids. You et al [74] reported a novel grafted and crosslinked copolymer starch as filtrate reducer. The copolymer was obtained through grafting and crosslinking starch with acrylic acid (AA), acrylamide (AM), N-vinylpyrrolidone (NVP), and N, N-methylene bis acrylamide (MBA) in aqueous solutions.…”
Section: Starch-based Filtrate Reducersmentioning
confidence: 99%
“…The remarkable advantages of starch nanosphere, such as insignificant influence on rheology, outstanding filtration control at elevated temperatures and high biocompatibility, make it a promising filtrate reducer in high-performance water-based drilling fluids. You et al [74] reported a novel grafted and crosslinked copolymer starch as filtrate reducer. The copolymer was obtained through grafting and crosslinking starch with acrylic acid (AA), acrylamide (AM), N-vinylpyrrolidone (NVP), and N, N-methylene bis acrylamide (MBA) in aqueous solutions.…”
Section: Starch-based Filtrate Reducersmentioning
confidence: 99%